PENGGUNAAN MEDIA PEMBELAJARAN KARTU KUARTET PERISTIWA DAN TOKOH SEJARAH MATERI SEJARAH KONTEMPORER PADA MAHASISWA JURUSAN PENDIDIKAN SEJARAH DAN SOSIOLOGI DI IKIP BUDI UTOMO MALANG - Irvan Lestari; Muhammad Naharuddin Arsyad (Khazanah Pendidikan, 2020)
ABSTRACTTeaching and learning activities should not only be carried out conventionally, such aslecturers lecturing and students listening. Learning history must have variations in itsimplementation, the use of media can be one way so that teaching and learning activitiesare not monotonous. Because history is the study of the past and historical narrativesdemand to be explained chronologically. Thus, a quartet card containing pictures ofevents and historical figures that are conceptualized in accordance with historicalproclamation, is expected to be able to facilitate the delivery of contemporary historicalmaterial as well as learning activities to be active. The purpose of this study was todetermine the effectiveness of the use of learning media quartet cards events andhistorical figures. This type of research is an experimental method, with one grouppretest posttest design research design. From the results of the Kolmogorov-Smirnovtest using SPSS 14 it was found that the research subjects were normally distributed andbased on the results of the Paired Samples Test t-test it was found that the sig value was0,000> 0.05. While the t -10.921 and for ttable at a significant level α = 5% (0.05) withdegrees of freedom (df) n-1 or 45-1 = 44. 2-sided testing (significance = 0.025) resultsare obtained for ttable at 2, 01537 with a significant level of 0.025. Obtained the resultsof -test <-table (-10,921 <-2,01537) then H0 is rejected and Ha is accepted. So it canbe concluded that the use of Learning Media Quartet Cards Events and HistoricalFigures Contemporary History Materials can improve the learning outcomes of studentsmajoring in history and sociology IKIP Budi Utomo Malang.Keywords: Quartet Card Media, Contemporary History, Learning Outcomes